2019
DOI: 10.1097/grf.0000000000000458
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Reduce Burnout and Improve Resilience: Impact on a Health System’s Outcomes

Abstract: With the continuously changing health care environment and dramatic shift in patient demographics, institutions have the responsibility of identifying and dedicating resources for maintaining and improving wellness and resilience among front line providers to assure the quality of patient care. Our institution, the Ohio State University Wexner Medical Center (OSUWMC), has addressed the goal to decrease burnout for providers in a multistep, multiprofessional, and multiyear program starting firstly with institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…Another study found that resilience reduces the impact of certain dimensions of burnout in critical care professionals . A study of medical residents who had participated in mindfulness programs and resilience training, showed a 26% reduction in burnout . This study also showed an increase in resilience scores associated with reduced safety events and improved patient satisfaction …”
Section: Introductionmentioning
confidence: 78%
“…Another study found that resilience reduces the impact of certain dimensions of burnout in critical care professionals . A study of medical residents who had participated in mindfulness programs and resilience training, showed a 26% reduction in burnout . This study also showed an increase in resilience scores associated with reduced safety events and improved patient satisfaction …”
Section: Introductionmentioning
confidence: 78%
“…Some learners faced complex stressors in the healthcare setting, such as high workloads, staff shortages, resource constraints, conflicts with coworkers, and meeting the many needs of patients and their families [ 65 , 66 , 68 70 , 92 , 102 , 103 ]. These challenges have been associated with job-related absenteeism, burnout, and high turnover rates, and can impact the delivery of high-quality patient care [ 66 , 67 , 71 , 72 , 93 , 101 ]. Other learners lacked specific skills and knowledge, which reduced clinical engagement with their patients [ 73 77 , 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…Burnout has been increasingly documented over the past decade, especially in high-stress professions such as HCPs 1,2,410,26,27 with health systems increasingly aware of the high costs associated with burnout. Mindfulness-based interventions addressing burnout among HCPs are in high demand as the evidence supporting the success of these interventions such as MIM is strong, 28,29 and the benefits span a range of outcomes.…”
Section: Discussionmentioning
confidence: 99%